Detecting Wahlund effects together with amplification problems: Cryptic species, null alleles and short allele dominance in Glossina pallidipes populations from Tanzania. (20th April 2019) - Manangwa, Oliver; De Meeûs, Thierry; Grébaut, Pascal; Ségard, Adeline; Byamungu, Mechtilda; Ravel, Sophie
Abstract: Population genetics is a convenient tool to study the population biology of non‐model and hard to sample species. This is particularly true for parasites and vectors. Heterozygote deficits and/or linkage disequilibrium often occur in such studies and detecting the origin of those (Wahlund effect, reproductive system or amplification problems) is uneasy. We used new tools (correlation between the number of times a locus is found in significant linkage disequilibrium and its genetic diversity, correlations between Wright's F IS and F ST, F IS and number of missing data, F IT and allele size and standard errors comparisons) for the first time on a real data set of tsetse flies, a vector of dangerous diseases to humans and domestic animals in sub‐Saharan Africa. With these new tools, and cleaning data from null allele, temporal heterogeneity and short allele dominance effects, we unveiled the coexistence of two highly divergent cryptic clades in the same sites. These results are in line with other studies suggesting that the biodiversity of many taxa still largely remain undescribed, in particular pathogenic agents and their vectors. Our results also advocate that including individuals from different cohorts tends to bias subdivision measures and that keeping loci with short allele dominance and/or too frequent missing data seriously jeopardize parameter's estimations. Finally, separated analyses of the two clades suggest very small tsetse densities and relatively large dispersal.